2020
DOI: 10.7150/ijbs.40042
|View full text |Cite
|
Sign up to set email alerts
|

Bisdemethoxycurcumin Enhances the Sensitivity of Non-small Cell Lung Cancer Cells to Icotinib via Dual Induction of Autophagy and Apoptosis

Abstract: Non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) wild-type is intrinsic resistance to EGFR-tyrosine kinase inhibitors (TKIs). In this study, we assessed whether the combination of bisdemethoxycurcumin (BDMC) and icotinib could surmount primary EGFR-TKI resistance in NSCLC cells and investigated its molecular mechanism. Results showed that the combination of BDMC and icotinib produced potently synergistic growth inhibitory effect on primary EGFR-TKI-resistant NSCLC cell lines H460… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In this progress, up-regulated APCDD1L-AS1 as a miRNA sponge to decoy miR-1322, miR-1972 and miR-324-3p, promote the expression of SIRT5, inhibit autophagic degradation of EGFR, increase EGFR phosphorylation, inhibit apoptosis and induce icotinib resistance EGFR-TKI-resistant NSCLC cells by negative feedback regulation of Akt/mTOR signaling and inducing autophagy, suggesting promising therapeutic strategy in NSCL C with EGFR-TKI resistant phenotype. In addition, a recent study reported that the combination of bisdemethoxy curcumin and icotinib could enhance the sensitivity of primary EGFR-TKI resistant NSCLC cell lines to icotinib via autophagy induction [41], which was similar to ours. Therefore, our study provided strong evidence that manipulating the activity of autophagy might be a useful therapeutic strategy to enhance the drug sensitivity in cancer [42,43].…”
Section: Discussionsupporting
confidence: 89%
“…In this progress, up-regulated APCDD1L-AS1 as a miRNA sponge to decoy miR-1322, miR-1972 and miR-324-3p, promote the expression of SIRT5, inhibit autophagic degradation of EGFR, increase EGFR phosphorylation, inhibit apoptosis and induce icotinib resistance EGFR-TKI-resistant NSCLC cells by negative feedback regulation of Akt/mTOR signaling and inducing autophagy, suggesting promising therapeutic strategy in NSCL C with EGFR-TKI resistant phenotype. In addition, a recent study reported that the combination of bisdemethoxy curcumin and icotinib could enhance the sensitivity of primary EGFR-TKI resistant NSCLC cell lines to icotinib via autophagy induction [41], which was similar to ours. Therefore, our study provided strong evidence that manipulating the activity of autophagy might be a useful therapeutic strategy to enhance the drug sensitivity in cancer [42,43].…”
Section: Discussionsupporting
confidence: 89%
“…An important point which is commonly neglected in numerous studies, is that 3-MA may also have an impact on RSV-induced apoptosis in A549 cells. Some studies have demonstrated that 3-MA pre-treatment led to a marked decrease in apoptosis (56,57), while in other cases 3-MA led to an increase in apoptosis (58,59). Additionally, certain studies have demonstrated that 3-MA does not cause an obvious change in the apoptotic cell population in a certain range of time and concentration (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the interplay between apoptosis and autophagy is complex and highly dependent on the cellular context and different treatments. Under certain circumstances, autophagy inhibits apoptosis or the activation of apoptosis is coupled to the suppression of autophagy (59,62), whereas in other instances, it acts synergistically with apoptosis and is even considered an upstream event of apoptosis (57,63). It also has been found that licochalcone A-induced autophagy is neither pro-nor anti-apoptotic (64).…”
Section: Discussionmentioning
confidence: 99%
“…While afatinib achieves superior efficacy in progression-free survival (PFS) and overall survival (OS) compared with conventional chemotherapy in NSCLC, progression inevitably occurs after EGFR TKI treatment for acquired resistance, which presents challenges in the treatment of NSCLC ( 7 , 8 ). The mechanisms of acquired resistance are classified into three types: acquired mutation of targetable driver genes, bypass of signaling pathway activation, and histological lineage-transformation ( 9 ). Accordingly, pharmacological interception of the propensity of tumor cells to bypass signaling pathways derails their signaling or adhesion receptors and may allow the identification of novel targets for cancer therapy ( 10 ).…”
Section: Introductionmentioning
confidence: 99%